2014
DOI: 10.1074/jbc.m114.558288
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy in Cisplatin Resistance in Ovarian Cancer Cells

Abstract: Background:The contribution of autophagy to acquired cisplatin resistance in ovarian cancer has not been studied. Results: Cisplatin treatment activates ERK and subsequently promotes autophagy and counteracts cisplatin-induced cell death. Inhibition of autophagy enhances cisplatin sensitivity. Conclusion: Cisplatin-induced autophagy contributes to cisplatin resistance. Significance: Targeting autophagy may overcome cisplatin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
181
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(194 citation statements)
references
References 47 publications
8
181
3
2
Order By: Relevance
“…Wang et al demonstrated that cisplatininduced autophagy is regulated by the ERK pathway, which is in turn associated with the Atg5 pathway (Wang and Wu, 2014). In our results, treatment with SSZ induced activation of ERK pathway ( Figure 7) and increased Atg5-12 complex ( Figure 5) respectively.…”
Section: Lc3-i Lc3-iisupporting
confidence: 66%
“…Wang et al demonstrated that cisplatininduced autophagy is regulated by the ERK pathway, which is in turn associated with the Atg5 pathway (Wang and Wu, 2014). In our results, treatment with SSZ induced activation of ERK pathway ( Figure 7) and increased Atg5-12 complex ( Figure 5) respectively.…”
Section: Lc3-i Lc3-iisupporting
confidence: 66%
“…Furthermore, PEBP1 did not affect MAPK/ERK activation following the treatment with cisplatin, an anticancer drug that generally activates the MAPK/ERK pathway to stimulate cell death in cancer cells and induces autophagy under certain conditions. [65][66][67] However, PEBP1 overexpression in HeLa cells significantly suppressed LC3-II, suggesting that PEBP1-dependent inhibition of autophagy does not require MAPK/ERK activity. These results were also observed in H1299 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, acquired resistance to cisplatin remains a major limitation of its success clinically in ovarian cancer. Increasing evidence indicates that autophagy plays an important role in the prosurvival and resistance against chemotherapy, however, the underlying mechanisms have not been fully elucidated (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%